Effect of the location and size of a single crack on first fundamental frequency of a cantilever beam using fiber optic polarimetric sensors and characterisation of FBG sensors - Maheshwari, Muneesh (2013)
Fiber Optics Polarimetric Sensors (FOPS), utilizing first fundamental frequency mode and its harmonics, have already been used as damage detection tool. The FOPS technology is attractive in damage detection as it facilitates us with real time non-destructive health monitoring of different mechanical and civil structures. In this paper, the effects of the size and the location of a single crack on the frequency of first fundamental mode of a cantilever beam have been studied. A relation between the relative size of a crack and relative change in the first fundamental frequency has been established theoretically and then verified experimentally. Further, it has been shown that the cracks, close to the fixed end of the cantilever beam, have significant effect on the frequency of first fundamental mode and as the crack moves away from the fixed end, the effect on the frequency starts becoming diminished. Also the sensitivity of Fiber Bragg Grating (FBG) sensor against a single crack has been studied along both the directions; parallel to the axis of FBG sensor and perpendicular to the axis of FBG sensor. Experimental results show that the range of sensitivity in both the directions is almost the same bur FBG is more efficient along its axis.